Exploring the Hemolymph of the Pill Millipede Arthrosphaera lutescens (Butler, 1872): Chemical Composition, Bioactive Properties, and Computational Studies - Priyanka Palakkaparambil; Veena Venugopal; Gouthami Vijayan; Mohammed Amjed Alsaegh; Varun Thachan Kundil; Arun Kumar Gangadharan; Ovungal Sabira; Aswathi; A. V. Raghu; Kodangattil Narayanan Jayaraj; Anthyalam Parambil Ajaykumar (Current Issues in Molecular Biology, 2025)
Most studies on the Arthrosphaera genus, or giant pill millipedes, focus on its taxonomy, distribution, and ecology. Therefore, this investigation aimed to explore the chemical composition and bioactive properties of the hemolymph of the giant pill millipede Arthrosphaera lutescens (Butler, 1872). Chemical characterization of hemolymph was performed using gas chromatography–mass spectrometry (GC-MS) and liquid chromatography–quadrupole time-of-flight mass spectrometry (LC-MS Q-TOF), revealing a complex array of over 200 compounds. The bioactive properties of hemolymph were determined by using radical scavenging capacity (DPPH assay); antibacterial activity against human pathogens like Escherichia coli (Migula, 1895) Castellani and Chalmers 1919, Klebsiella pneumonia (Schroeter, 1886) Trevisan 1887, and Staphylococcus aureus (Rosenbach, 1884); and cytotoxicity against Dalton’s lymphoma ascites (DLA) cells using the trypan blue assay. The hemolymph showed radical scavenging properties and antibacterial and cytotoxic activity. Among the identified metabolites, 1,2-dimethoxy-13-methyl-[1,3]benzodioxolo[5,6-c]phenanthridine (DMBP) emerged as a promising candidate due to its high abundance and bioactivity profile, showcasing therapeutic potential against both lymphoma and S. aureus in further docking studies. Computational analysis identified key T-cell lymphoma targets, with molecular docking suggesting DMBP’s anticancer properties through interactions with proteins like AKT1 and mTOR. Additionally, docking revealed DMBP’s antibacterial effects via interactions with proteins such as Sortase-A and DNA gyrase. This research underscores the potential pharmaceutical applications of metabolites from giant pill millipedes.